Analisis Risiko Kecelakaan Kerja dengan Metode Failure Mode Effect Analysis (FMEA) pada PT. Sermani Steel Corporation - Anugrah M, Erlangga (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to analyze the risk of work accidents at PT Sermani Steel Corporation using the Failure Mode Effect Analysis (FMEA) method. This method is applied to identify potential hazards in the production process of zinc coated steel, such as hollow, C channel, and battens. Data were collected through questionnaires, observations, and interviews, then processed to calculate the Risk Priority Number (RPN). The results showed that the highest risk was found in zinc machine production activities, with an RPN value of 321.6, mainly related to the risk of being cut by products or product debris. Based on Pareto and Fishbone Diagram analysis, the main causes of accidents are human, machine, method, and environmental factors. The conclusions emphasize the importance of OHS training, installation of signs and indicator lights on machines, and close supervision to minimize the risk of accidents. The recommendations provided are expected to reduce work accidents by 38% of the total accidents that occur in the production area.